Evaluation and Socialization of Health Protocol at SDN Jati 1 Tarogong Kaler Garut - Siva Hamdani (Indonesian Journal of Community Empowerment (IJCE), 2022)
Abstract At this time there are not many treatments for Covid-19, but one way to avoid the spread of the Covid-19 virus is to vaccinate and adhere to health protocols. Health protocols are the key to protect themselves and those around them from the dangers of Covid-19. With the increase in positive cases in children, there is a need for socialization and education about complying with health protocols, especially during school. The purpose of this activity is to educate students at SDN Jati 1 to always comply with health protocols. The data were taken using an evaluation questionnaire before and after socialization related to health protocols in groups, thematic KKN Jati Village Group 3. The method of presenting data was descriptive in the form of graphs. The results of the evaluation showed that there were differences between the data before and after the socialization which showed that after the socialization the students could understand the material related to health protocols. Abstrak Pada saat ini pengobatan untuk penyakit Covid-19 belum banyak ditemukan, namun salah satu cara untuk menghindari penyebaran virus Covid-19 ini dengan melakukan vaksinasi dan mematuhi protokol kesehatan. Protokol kesehatan merupakan kunci agar melindungi diri dan sekitar dari bahaya Covid-19 Dengan meningkatnya kasus positif pada anak-anak maka perlunya sosialisasi dan edukasi mengenai mematuhi protokol kesehatan terutama pada masa sekolah. Tujuan dari kegiatan ini adalah mengedukasi para siswa di SDN Jati 1 untuk selalu mematuhi protokol kesehatan. Data diambil menggunakan kuesioner evaluasi sebelum dan setelah sosialisasi terkait protokol kesehatan secara berkelompok KKN Tematik Desa Jati Kelompok 3. Metode penyajian data secara deskriptif berupa grafik. Hasil evaluasi diperoleh bahwa terdapat perbedaan antara data sebelum dan sesudah dilakukan sosialisasi yang menunjukkan bahwa setelah sosialisasi para siswa dapat memahami materi terkait protokol kesehatan.